STRATEGI BERTAHAN HIDUP KELUARGA PEDAGANG PENGECER CAKAR DI PASAR TERONG KOTA MAKASSAR - Astria Astria; Idham Irwansyah; Mario Mario S.M (PREDESTINATION: Journal of Society and Culture, 2020)
This study aims to determine the profile of socio-economic life and the strategy of family survival of the claw retailers in Pasar Terong, Makassar City. The retrieval of informants in the study was carried out by purposive sampling with 12 families of informants. In this study, researchers used observation data collection techniques, interviews and documentation. The analysis technique used is qualitative data analysis techniques, descriptive in nature (prior analysis in the field and data analysis in the field). The results showed that the profile of the socio-economic life of the claw retailers family was not yet feasible. The family survival strategies of claw retailers include active strategies (family members participate in earning a living and sell leftovers to pa'lever or pa'drop), passive strategies (making savings and saving) and network strategies (making loans and receiving assistance from the government) .